2019
DOI: 10.1371/journal.pone.0215646
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of biomechanical and collagen heterogeneity in uterine fibroids

Abstract: Objective Uterine fibroids (leiomyomas) are common benign tumors of the myometrium but their molecular pathobiology remains elusive. These stiff and often large tumors contain abundant extracellular matrix (ECM), including large amounts of collagen, and can lead to significant morbidities. After observing structural multiformities of uterine fibroids, we aimed to explore this heterogeneity by focusing on collagen and tissue stiffness. Methods For 19 fibroids, ranging in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…With the same indication, evidence of biomechanical and biochemical heterogeneity in uterine fibroids has just been reported. The authors observed heterogeneity in structure, collagen content, and stiffness highlighting that fibroid regions differ in biochemical status and they suggest that these differences might be associated with variations in local pressure, biomechanical signaling, and altered growth 68 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…With the same indication, evidence of biomechanical and biochemical heterogeneity in uterine fibroids has just been reported. The authors observed heterogeneity in structure, collagen content, and stiffness highlighting that fibroid regions differ in biochemical status and they suggest that these differences might be associated with variations in local pressure, biomechanical signaling, and altered growth 68 .…”
Section: Discussionmentioning
confidence: 96%
“…For instance, collagen density distributions in human knee ligaments were documented to quantify differences in density within and between these ligaments 69 . Very recently, heterogeneity in structure, collagen content, and stiffness in uterine fibroids was reported 68 . Thus, it is interesting to evaluate if this heterogeneity is expressed also in terms of density distributions, as it was shown in human knee ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…Sastoje se od glatkih mišićnih ćelija, fibroblasta i ekstracelularnog matriksa [3]. Obilna količina ekstracelularnog matriksa, koju grade glikozaminoglikani i gusto zbijeni intersticijumski kolagen, čini tkivo mioma dva do četiri puta čvršćim od miometrijuma [4]. Ovi tumori su jasno ograničeni od okolnog tkiva pseudokapsulom, koja nastaje kao rezultat kompresije miometrijuma njihovim progresivnim rastom.…”
Section: Uvodunclassified
“…They consist of smooth muscle cells, fibroblasts and extracellular matrix [3]. A profuse amount of extracellular matrix, which is made up of glycosaminoglycans and densely packed interstitial collagen, makes the myoma tissue two to four times firmer than the myometrium [4]. These tumors are clearly delineated by a pseudocapsule which separates them from the surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…These properties are related to the local pressure, biochemical signals and altered growth. 2 Many fibroids are discovered incidentally in asymptomatic women upon clinical or ultrasonographic examination. 3 Age and ethnicity are risk factors for UF development and growth, and they may be present in up to 70% of perimenopausal women.…”
Section: Introductionmentioning
confidence: 99%